Characterization of Aspergillus Niger 65i6 lipase from solid-state fermentation using Jatropha seed cake medium - Chusnul Hidayat; Sari Darmasiwi; Maulina Nurikasari; Muhammad Nur Cahyanto (Universitas Gadjah Mada, 2015)
Jatropha curcas seed cake contains a high amount of protein, and consequently has very high potentialas a medium for lipase production. The objective of this research was to characterize lipase from Aspergillusniger 6516, which was produced by solid-state fermentation on Jatropha curcas seed cake as the medium. The effects of pH and temperature on enzyme activity were evaluated, along with substrate specifcity and enzyme stability. Fermentation was performed at a water concentration of 63% and temperature of 30 °C for 7 days. The results showed that the optimum pH and temperature for Aspergillus niger 6516 lipase activities were 8.0 and 40 °C, respectively. The lipase had the substrate specifcity to hydrolyze long-chain fatty acids and was stable in polar organic solvents. The lipase had a molecular weight, Km and vmax about 19 kDa, 0.27 µmol/ml, and 52.63 µmol/ml/min, respectively. The results also suggested that the produced lipase from Aspergillus niger 6516 was an alkaline lipase. Based on these results, we conclude that Jatropha seed cake is a suitable medium for lipase production.